Nilai Pembinaan Karakter dan Moral dalam Novel Dendam Si Yatim Piatu Karya Sintha Rose - Karsiti Karsiti; Restoeningroem Restoeningroem (Diskursus: Jurnal Pendidikan Bahasa Indonesia, 2021)
This study aims to describe and explain the values of character and moral development contained in the novel “Dendam” Si Yatim Piatu by Sintha Rose. The sample in this study is the novel "Dendam" Si Orphan by Sintha Rose. The research approach used by the researcher in analyzing the novel “Dendam” Si Yatim Piatu by Sintha Rose is a pragmatic approach as a content analysis study. The data was collected using reading and note-taking techniques. Data analysis uses descriptive qualitative statistics such as evidence of the value of character and moral development in the novel "Dendam" Si Yatim Piatu by Sintha Rose. The number of findings of evidence of the value of character building include: the number of findings of religious evidence 42 (33.6%), the number of findings of honest evidence 4 (3.2%), the number of findings of evidence of tolerance 0 (0%), the number of findings of disciplinary evidence 7 ( 5.6%), the number of hard work evidence findings 6 (4.8%), the number of creative evidence findings 6 (4.8%), the number of independent evidence findings 5 (4%), the number of democratic evidence findings 8 (6.4 %), the number of findings of evidence of curiosity 4 (3.25%), the number of findings of evidence of enthusiasm 0 (0%), the number of findings of evidence of love for the homeland 1 (0.8%), the number of findings of evidence of appreciating achievement 4 (3, 2%), the number of findings of friendly/communicative evidence 13 (10.4%), the number of findings of evidence of peace-loving 3 (2.4%), the number of findings of evidence of fondness of reading 5 (4%), the number of findings of evidence of caring for the environment 3 (2 ,4%), the number of findings of evidence of social care 3 (2.4%), the number of findings of evidence of responsibility 11 (8.8%). While the number of findings of evidence of the value of moral development include: the number of findings of evidence of piety 9 (7.9%), the number of findings of evidence of tawakal/surrender 7 (6.1%), obedient 7 (6.1), diligent 7 (6.1 %), polite 6 (5.3%), optimistic 8 (7%), positive thinking 3 (2.6%), never giving up 5 (4.4%), empathy 5 (4.4%), open-minded 5 (4.4%), compassion 28 (24.6%), help 3 (2.6%), simplicity 4(3.5), persistence 10 (8.8%).Value of Coaching; Character; Moral